(untitled) (PERcursos Linguísticos, 2023)
In recent years, the mobilizations of women around the right to legal abortion have increased. These initiatives have been successful in some Latin American countries, such as Mexico and Colombia, where abortion practice was decriminalized by judicial decision. In this regard, this article applies the theoretical framework of Systemic-Functional Linguistics (HALLIDAY, 2004; CUNHA; SOUZA, 2011) to verify how the press of these nations reverberated the decriminalization and how the women and the Court were described in these episodes, with an emphasis on the transitivity system and its processes and participants. Ultimately, it sought to identify whether the country and position of the newspaper influenced the choice of such elements. To achieve these goals, this work analyzed six editorials (three from Mexico and three from Colombia) published in the days after abortion decriminalization in each of these territories. The results indicate that women’s processes and participants were mostly determined by the country of the newspaper, whereas those of the Court were mainly influenced by the journal’s opinion on the judicial resolution.